Low Ripple Charge Pump Based Voltage Regulator For Low Voltage Application - Lee Fu, New (2014)
In power supply systems, charge pump circuits are typically cascaded with low dropout (LOO) regulator to suppress systematic noise and to provide low noise output. By providing lower output ripple voltage from charge pump circuit, input voltage ripple (noise) can be reduced first before it is fed into LOO and hence a more stable supply voltage can be generated from LOO. In this project, a new low voltage CMOS charge pump circuit which offers lower output ripple voltage is proposed. The newly proposed charge pump circuit is formed by the combination of cross-coupled charge pump circuit and the Charge-Transfer-Switch (CTS) control schemes. It has eliminated the backward leakage current of cross-couple charge pump circuit, which eventually gives smaller output ripple voltage and hence, a more stable output voltage.